PENGARUH KOHESIVITAS KELOMPOK TERHADAP KINERJA KARYAWANPADA PT. KERTA RAJASA RAYA KABUPATEN SIDOARJO - MALIK, ABDUL (Jurnal Ilmu Manajemen (JIM), 2017)
The development of the global industry era makes the business world in Indonesia become more rapidly. This makes more and more companies established, so the more intense competition antra company in achieving its goals. A company if you want to compete in the speed of business growth, then the company must pay attention to human resources (HR) or employees such as group cohesiveness and employee performance to assist companies in achieving goals. The purpose of this study was to examine and analyze the effect of group cohesiveness on employee performance at PT. Kerta Rajasa Raya Kabupaten Sidoarjo. This research was a quantitative using 45 people as sample. Measuring instrument used in this study were interviews, observation, and questionnaires. Analysis of the data using Partial Least Square (PLS) with the helpof SmartPLS 3.0 and Statistical Package for the Social Science (SPSS) software. This study used a Likert scale as the scale of measurement. The results showed that group cohesivenessinfluence the employee performance. Keywords: Group Cohesiveness, Employee Performance<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />